Varamon public bath; a vision for the future development of the former folk park area - Elfström, Jakob (My University, 2025)
Since the establishment of Motala folk park and the outdoor swimming area Mariebergsbadet in 1976 in the Varamon beach area in Motala, the location has served as an important meeting place for the city’s population and visitors for several decades. Here, people have gathered and socialized through music, dance, politics, play and swimming. In 2016, the Danish company Parken Sport & Entertainment initiated plans for an establishment of a large holiday resort in the Varamon area. The folk park area became one of the sites designated for the new development. In 2021, Motala municipality decided to demolish all existing buildings in the Folk Park area to free up space for the new development, but the detailed plans for the holiday resort had not yet been approved. Due to a lengthy process of appeals against the establishment, the Danish company decided in January 2024 to cancel their plans for a development in Motala. Today, the folk park area stands empty without any clear plans for how the site should be developed in the future. The purpose of this master’s thesis is to present a vision for the site’s future development, based on the collective memory of the area as well as an analysis of the city’s current needs. The program includes a public bath, holiday accommodations and spaces for dance, music, food, play and sports, as such a program would serve an important function for the population of Motala and contribute to increased visitor establishment in the Varamon area. The project includes an overall plan of the entire area, while the design of the public bath is the main focus where an in-depth exploration of wood construction has been used as an approach both constructively and architecturally in the design. The focus on wood construction has shaped this project, using structure and materials to define the spatial character and create rhythm. A key challenge was organizing the complex program into a well-integrated building form. Dividing the building into multiple volumes allowed for contextual adaptation, enhanced views, and a mix of intimate and generous spaces with clear flows and dynamic spatial sequences.
Keywords: public bath, outdoor bath, swimming hall, wood construction, glulam